Development of a Production Planning and Control Software in Total Productivity Maintenance Environment - Lee, Pang Seng (2004)
Successful modern manufacturing organizations require support from both effective and efficient maintenance works. One of the approaches for improving the performance of both production and maintenance is by developing and implementing a Total Productive Maintenance (TPM) strategy. The main objectives for this study is to develop a production planning and control (PPC) software in a TPM environment for a manufacturing company and improve the overall production planning and control system from manual recording to computer aided recording which includes some planning features such as Master Production Scheduling (MPS), monthly capacity planning, operation scheduling and other requirements. A TPM based software program has been developed to ease the process of production planning and control in TPM environment by executing sequential methodology such as problem identification, literature review, problem formulation, data coliection, company operation review, flow chart system and program algorithm before test run in the company. This program has been created in Window format and encoded using Microsoft Visual Basic 6.0. This software was tailored design based on the present operation at Earntrade Industries which practise Earliest Due Date (EDD) and Short Processing Time (SPT) performance measures. This software has been evaluated at Earntrade Industries for a period of two months to test the overall performance of the application software relevant to the project goal. The system which change from manual to computer aided recording manage to decrease the handling time from manual to computer aided recording by 89.22 % and avoid 100% unwanted human error.